Upaya Penyuluh Agama Islam Dalam Meminimalisir Cerai Goib Di Kantor Urusan Agama (KUA) Sangatta Utara - Purnoto, Purnoto; Andaryuni, Lilik (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2024)
Abstract Divorce, especially divorce Ģoib, is a complex social phenomenon that affects individuals and society with significant repercussions. In Indonesia, the Office of Religious Affairs (KUA) plays an important role in addressing this issue through Islamic religious counseling. This study examines the efforts of Islamic religious counselors in minimizing cases of divorce ģoib in the area of KUA Sangatta Utara, East Kutai. This study used a qualitative approach with a case study as its design. Data were collected through participant observation, in-depth interviews, and document analysis. The findings show that Islamic religious instructors actively provide education on Islamic marriage law, the importance of the presence of both parties in divorce, and the negative impact of divorce. They also act as mediators to resolve household conflicts and provide spiritual counseling to couples experiencing problems. Challenges faced include a lack of community awareness of Islamic marriage law, limited KUA resources, and socio-economic issues. Nonetheless, Islamic religious counseling has succeeded in reducing the divorce rate by increasing community understanding and awareness. The results of this study indicate that the efforts of Islamic religious extension are effective in minimizing divorce cases by using a holistic and integrated approach. Recommendations include intensification of extension programs, expansion of outreach, and increased collaboration across institutions to increase effectiveness in dealing with divorce. Keywords: Islamic Religious Counselors, Divorce Minimization, Divorce Ģoib Abstrak Perceraian, khususnya cerai Ģoib, merupakan fenomena sosial kompleks yang mempengaruhi individu dan masyarakat dengan dampak yang signifikan. Di Indonesia, Kantor Urusan Agama (KUA) memegang peran penting dalam menangani masalah ini melalui penyuluhan agama Islam. Penelitian ini mengkaji upaya penyuluh agama Islam dalam meminimalisir kasus cerai ģoib di wilayah KUA Sangatta Utara, Kutai Timur. Studi ini menggunakan pendekatan kualitatif dengan studi kasus sebagai desainnya. Data dikumpulkan melalui observasi partisipan, wawancara mendalam, dan analisis dokumen. Temuan menunjukkan bahwa penyuluh agama Islam aktif memberikan edukasi tentang hukum perkawinan Islam, pentingnya kehadiran kedua belah pihak dalam perceraian, dan dampak negatif dari cerai ģoib. Mereka juga berperan sebagai mediator untuk menyelesaikan konflik rumah tangga dan memberikan konseling spiritual kepada pasangan yang mengalami masalah. Tantangan yang dihadapi termasuk kurangnya kesadaran masyarakat akan hukum perkawinan Islam, keterbatasan sumber daya KUA, dan masalah sosial-ekonomi. Meskipun demikian, penyuluhan agama Islam telah berhasil mengurangi angka cerai ģoib dengan meningkatkan pemahaman dan kesadaran masyarakat. Hasil penelitian ini menunjukkan bahwa upaya penyuluh agama Islam efektif dalam meminimalisir kasus cerai ģoib dengan menggunakan pendekatan yang holistik dan terintegrasi. Rekomendasi yang diajukan mencakup intensifikasi program penyuluhan, perluasan jangkauan, dan peningkatan kolaborasi lintas lembaga untuk meningkatkan efektivitas dalam menangani perceraian. Kata kunci: Penyuluh Agama Islam, Meminimalisir Perceraian, Cerai Ģoib